Living with Mount Mabo: povoados, land, and nature conservation in contemporary Mozambique - Matusse, Anselmo (School of African and GenderStuds, Anth and Ling, 2021)
Based on ethnographic fieldwork in the povoados of Nvava and Nangaze, in the district of Lugela, Zambézia Province, central Mozambique, consisted of field visits that started in June 2016 and ended in April 2018, this thesis is an ethnography of the relationships between people, spirits, animals and landscapes. It examines the cultural, scientific, ethical, and economic stakes of local modes of relating to Mount Mabo, the River Múgue and Mount Muriba that both abide by and surpass the exclusionary forms of science, nature conservation and governance that dominate environmentalism in Mozambique. Focusing on narratives and practices, the study explores concepts such as person, nature and time as mobilized by the state, conservationists and local residents, and describe the respective emerging worlds and their messy interconnections, namely, the conservationists' "Google Forest" premised on techno-science and modernist ideals and seeking to enact a divide between nature and society, the "Neo-extractive" version of landscapes promoted by the Frelimo-run state in its attempt to generate wealth and alleviate poverty also premised on techno-science and modernist ideals that construct nature as a natural resource and "public good" to be owned through DUATs (land use rights certificates) that only the state can grant or revoke; and finally, the "Secret Mount Mabo" as experienced and expressed by local residents whereby landscapes emerge as relational entities demanding ori'a (respect) from the humans with whom they engage in a relation of mutual belonging. In this world, the amwene emerge as the ones who control access to the mountain and forest through their ritual and spiritual power. The study finds that reframing of colonial and neoliberal notions of property, nature, labour and citizenry by conservationists and the state, underlies their technoscientific approaches seeking to protect nature from devastation and impose and their respective versions of nature, human and time—worlds—on local residents. That approach renders dialogues across ontologies extremely difficult. Working with local residents' concepts and practices the study proposes that Mount Mabo conservation efforts are at odds with local ontologies. While these are central to local residents and their practices of world-making, such ontologies occupy a marginal role in conservation project planning, design, and implementation, amid conservationists' attempts to mobilize local residents' alliance in nature protection. These observations draw from and reinterpret contemporary scholarship on political ecology, political ontology, Africanist thought, and decolonial theory, in that they account for different ecological practices and concepts that are linked to practices of wealth redistribution, recognition of other non-modernist ontologies and their colonial legacies. The study proposes that understanding and accounting for these differences and the ways they are made to endure or resisted could help in finding alternatives conducive to ensuring both ecological and local residents' wellbeing in ways that advance decoloniality in Mozambique.